Optimización de la aceptabilidad de un pan integral enriquecido con harina de maca (Lepidium meyenii Walp). - Requelme Vasquez, Juan Jesus (2019)
The objective of the present work was to develop an integral bread enriched with maca flour (Lepidium meyenii Walp) of high acceptability. A rotational central composite design of 22 was used including 4 axial and 3 central; which allowed to obtain the models that define the behavior of the independent variables of substitution percentage of maca flour (9 to 12%) and baking time (19 to 21 minutes) with respect to the dependent that was the general acceptability. Both the cooking time (linear, quadratic) and flour substitution (linear, quadratic) are significant (p <0.05) whereas the interaction between both variables does not significantly affect the model; thus, it is possible to construct the response surface for this, the STATISTICA 7.0 software was used. It was verified that when the substitution values of maca flour between 9 and 12%, and a cooking time of 19 and 21 minutes, the general acceptability reaches values close to or greater than 7.